The Effect of Head Up Cardiopulmonary Resuscitation on Cerebral and Systemic Hemodynamics. (May 2016) - Ryu, Hyun Ho; Moore, Johanna C.; Yannopoulos, Demetris; Lick, Michael; McKnite, Scott; Shin, Sang Do; Kim, Tae Yun; Metzger, Anja; Rees, Jennifer; Tsangaris, Adamantios; Debaty, Guillaume; Lurie, Keith G.
Abstract: Aim: Chest compressions during cardiopulmonary resuscitation (CPR) increase arterial and venous pressures, delivering simultaneous bidirectional high-pressure compression waves to the brain. We hypothesized that this may be detrimental and could be partially overcome by elevation of the head during CPR. Measurements: Female Yorkshire farm pigs (n = 30) were sedated, intubated, anesthetized, and placed on a table able to elevate the head 30° (15 cm) (HUP) and the heart 10° (4 cm) or remain in the supine (SUP) flat position during CPR. After 8 minutes of untreated ventricular fibrillation and 2 minutes of SUP CPR, pigs were randomized to HUP or SUP CPR for 20 more minutes. In Group A, pigs were randomized after 2 minutes of flat automated conventional (C) CPR to HUP (n = 7) or SUP (n = 7) C-CPR. In Group B, pigs were randomized after 2 minutes of automated active compression decompression (ACD) CPR plus an impedance threshold device (ITD) SUP CPR to either HUP (n = 8) or SUP (n = 8). Results: The primary outcome of the study was difference in CerPP (mmHg) between the HUP and SUP positions within groups. After 22 minutes of CPR, CerPP was 6 ± 3 mmHg in the HUP versus -5 ± 3 in the SUP (p = 0.016) in Group A, and 51 ± 8 versus 20 ± 5 (p = 0.006) in Group B. Coronary perfusion pressures after 22 minutes were HUP 6 ± 2 vs SUP 3 ± 2 (p = 0.283) in Group A and HUP 32 ± 5 vs SUP 19 ± 5, (p = 0.074) in Group B. In Group B, 6/8 pigs were resuscitated in both positions. No pigs were resuscitated in Group A. Conclusions: The HUP position in both C-CPR and ACD + ITD CPR significantly improved CerPP. This simple maneuver has the potential to improve neurological outcomes after cardiac arrest.